Cavalleria rusticana melodramma in one act - Mascagni, Pietro 1863-1945 (Arthaus Musik, 2012)
In a Sicilian village it is Easter Sunday. Santuzza's former lover Turiddu is in love with Lola, Alfio's wife. Santuzza seeks revenge by telling Alfio of Lola's unfaithfulness and he kills Turiddu in a fight, after the latter has left Santuzza in the charge of his mother